Primulina mabaensis (Gesneriaceae), a new species from a limestone cave of northern Guangdong, China - Chung, Kuo-Fang; Huang, Han-Yau; Peng, Ching-I; Xu, Wei-Bin (Phytotaxa, 2013)
We describe and illustrate the new species Primulina mabaensis from northern Guangdong, China. Its generic placement in the recently recircumscribed Primulina is confirmed by phylogenetic analyses of ITS and trnL-F intron-spacer DNA sequences. Primulina mabaensis is similar to P. repanda var. guilinensis, differing from the latter by its much larger flowers with corollas 2.5–3.0 cm (vs. 8–10 mm) long and corolla tubes 2.0–2.5 cm (vs. 6–8 mm) long and ca. 7 mm (vs. ca. 3 mm) in diameter at the corolla mouth. Primulina mabaensis is currently only known from limestone caves and rock surfaces of a karst tower in the Maba Man Archeology Site.